Externally Bonded GFRP Composites as a Structural Enhancement Technique for Shear Strengthening of Reinforced Concrete Beam - N. B. Bhopale; A. S. Manjarekar; C. S. Patil (International Journal of Scientific Research in Civil Engineering, 2024)
The rehabilitation, repair and strengthening of existing reinforced concrete (RC) structures is essential due to factors such as aging, steel reinforcement corrosion, construction/design defects, increased service loads demand, seismic events, and advancements in design guidelines. Fiber-reinforced polymers (FRP) are now being recognized as a promising material for the rehabilitation of such structures, through strengthening or repairing. In buildings and bridges, RC sections are commonly found in the form of beams and girders. Shear failure of RC beams is particularly due to its sudden occurrence without warning. Therefore, the utilization of externally bonded (EB) FRP composites for shear strengthening of RC beams has gathered popularity as a structural enhancement technique, primarily due to advantages of FRP composites, such as high strength-to-weight ratio and exceptional corrosion resistance. In addition, FRP repair systems give a cost-saving choice to traditional repair methods and materials. A study was performed to analyse the shear characteristics of RC beams enhanced with continuous glass fiber-reinforced polymer (GFRP) sheets. Reinforced concrete beams externally bonded GFRP sheets subjected to failure using a symmetrical two-point concentrated static loading system. The experimental data obtained included load, deflection, and failure modes of each beam, along with the effect of the number and orientation of GFRP layers on the beams' The failures observed in strengthened beams typically commence with the debonding of the FRP sheets, followed by brittle shear failure. The shear capacities of these beams were higher than that of the control beam.
Keywords: Rehabilitation; RC; GFRP; Shear Strengthening; Externally Bonded